IMPROVEMENT OF PUBLIC SERVICE QUALITY THROUGH REGIONAL BLOSSOMING POLICY (A Study at Ciater Sub-district Resulted from Regional Blossoming of Jalancagak Sub-district Subang Regency West Java) - Mulyawan, Rahman; Suwaryo, Utang; Saefulrahman, Iyep (Advances in Social Sciences Research Journal, 2017)
A requirement of adjacency between government and those who are governed is important if the government aim to provide a proper service. It reflects in one of the policy of Subang Regency Government called regional blossoming (pemekaran wilayah) that refers to the splitting up of their sub-districts (kecamatan) into multiple new territorial administrative units. The research is aimed at gaining a deep analysis on the policy through public service perspective and assisted by qualitative approach in the matter of data collection such as unstructured interview and documentation. The findings reveals the quality improvement of public service is an impact of regional blossoming in a certain local government. Furthermore, the regional blossoming policy also shows the more desirable presence of government amidst the public and also it is able to restrict a span of control and leadership of Camat as the determinant of adjacency embodiment between government and those who are governed and to embody a proper implementation of public service at once. Keywords: public service, district partition, the closeness of the government and the governee, leadership